Quantitative analysis of active labour population migrations - the case of Croatia - Perić Kaselj, Marina (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2021)
Migrations are a worldwide phenomenon occurring for centuries and an ongoing topic among numerous researchers. As such, global migrations have an impact on the labour market and the economy, Croatia being no exception. A dynamic history of migrations resulted in Croatia being labelled as a traditional emigration country. With the global financial crisis in 2008, an increasing number of active-labour population is migrating from Croatia to, mainly, developed European countries. After Croatia's accession to the European Union in 2013, a new market and new opportunities opened up for job seekers. In a time when more and more individuals are emigrating and a continuous need for active labour population is emerging, the question of the scale of migrations is raised. The article investigates how wages and unemployment influenced migrations in Croatia between 2007 and 2016. The data was tested using a multiple regression model and additionally confirmed by the MAPE. The obtained results confirm the significance of the model and its parameters.
Keywords: brezposelnost; delovne migracije; Hrvaška; MAPE; plače; povprečna absolutna odstotna napaka (MAPE); trg delovne sile; večkratna regresija